PENGEMBANGAN KOPERASI UNIT DESA MELALUI INTERVENSI PT. INTI INDOSAWIT SUBUR DI KAMPUNG DELIMA JAYA KECAMATAN KERINCI KANAN KABUPATEN SIAK - Rizkiyani, Atikah; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
KUD development carried out by PT. Inti Indosawit Subur has the involvement and cooperation of each other to improve the welfare of farmers or their communities. The KUD that manages in the field of oil palm plantations is currently inactive and is in the process of being developed by the company. This study aims to determine the process of Village Unit Cooperative Development through PT. Inti Indosawit Subur in Delima Jaya Village, Kerinci Kanan Subdistrict, Siak Regency and know what are the factors that inhibit the development of the Village Unit Cooperative Mulus Rahayu. This study uses the theory of Potter's Organizational Development in Sujianto, namely there are 5 stages of entry, sensing, lock-on, implementation, saparation which are the process of organizational development or Village Unit Cooperative in Delima Jaya Village, Kerinci Kanan District, Siak Regency. This type of research is qualitative using interviews, observation, and documentation. The research resulted in the findings that: first, in the process of the Development of Cooperative Village Units in Kampung Delima Jaya which was developed by the company based on the 5 stages above is still not optimal and the constraints occur at the lock-on stage namely what is the priority program. Furthermore, in the implementation phase (implementation) is still not running fully, what saparation stage is the goal of the final determination that is the status of the cooperative is currently not active and is still in the process of development stage and it is estimated that in 2020 the cooperative can be active again. Second, the inhibiting factors of KUD development are: Community responsiveness, limited human resources.Â Keywords : Organizational Development, Entry, Sensing, Lock-On, Implementation, Saparation